CTA - CENTRO DE TREINAMENTO, APERFEIÇOAMENTO, CAPACITAÇÃO EM TECNOLOGIAS AVANÇADAS - Campos, Maurício d.; Rech, Cassiano; Salvadori, Fabiano; Bolacell, Julio C. O.; Camargo, Robinson F. d. (Salão do Conhecimento, 2013)
Resumo